The impact of CEO turnover on equity volatility - Matthew J. Clayton; Jay C. Hartzell; Joshua V. Rosenberg (Federal Reserve Bank of New York, 2003)
A change in executive leadership is a significant event in the life of a firm. This study investigates an important consequence of a CEO turnover: a change in equity volatility. We develop three hypotheses about how changes in CEO might affect stock price volatility, and test these hypotheses using a sample of 872 CEO turnovers over the 1979-95 period. We find that volatility increases following a CEO turnover, even when the CEO leaves voluntarily and is replaced by someone from inside the firm. Forced turnovers increase volatility more than voluntary turnovers - a finding consistent with the view that forced departures imply a higher probability of large strategy changes. For voluntary departures, outside successions increase volatility more than inside successions. We attribute this volatility change to increased uncertainty over the successor CEO's skill in managing the firm's operations. We also document a greater stock price response to earnings announcements following CEO turnover, consistent with more informative signals of value driving the increased volatility. Our findings are robust to controls for firm-specific characteristics such as firm size, changes in firm operations, and changes in volatility and performance prior to the turnover.
Keywords: G34; G14; 330; Executives; Stock - Prices; Labor turnover; Führungskräfte; Börsenkurs; Volatilität; USA